An analysis of the frequency of Y‐chromosome microdeletions and the determination of a threshold sperm concentration for genetic testing in infertile men. (9th September 2018) - Johnson, Mark; Raheem, Amr; De Luca, Francesco; Hallerstrom, Marcus; Zainal, Yasmeen; Poselay, Sameer; Mohammadi, Baharak; Moubasher, Amr; Johnson, Thomas Frederick; Muneer, Asif; Sangster, Philippa; Ralph, David J.
Abstract : Objective: To describe the prevalence of Y‐chromosome microdeletions in a multi‐ethnic urban population in London, UK. To also determine predictive factors and a clinical threshold for genetic testing in men with Y chromosome microdeletions. Patients and Methods: A retrospective cohort study of 1473 men that were referred to a tertiary Andrology centre with male factor infertility between July 2004 and December 2016. All had a genetic evaluation, hormonal profile and 2 abnormal semen analyses. Those with abnormal examination findings also had targeted imaging performed. Results: The prevalence of microdeletions was 4% ( n = 58) in this study. These microdeletions were partitioned into the following regions: Azoospermia factors (AZF); AZFc (75%), AZFb+c (13.8%), AZFb (6.9%), AZFa (1.7%), and partial AZFa (1.7%). A high follicle‐stimulating hormone level ( P < 0.001) and a low sperm concentration ( P < 0.05) were both found to be significant predictors for the identification of a microdeletion. Testosterone level, luteinising hormone level and testicular volume did not predict the presence of a microdeletion. None of the men with an AZF microdeletion had a sperm concentration of >0.5 million/mL. Lowering the sperm concentration threshold to this level retained the high sensitivity (100%) and increased the specificity (31%). This would produce significant cost savings when compared to the European Academy of Andrology/European Molecular Genetics Quality Network and European Association of Urology guidelines. The surgical sperm retrieval (SSR) rate after microdissection testicular sperm extraction was 33.2% in men with AZFc microdeletion. Conclusions: The prevalence of Y‐chromosome microdeletions in infertile men appears to vary between populations and countries. A low sperm concentration was a predictive factor ( P < 0.05) for identifying microdeletions in infertile males. A threshold for genetic testing of 0.5 million/mL would increase the specificity and lower the relative cost without adversely affecting the sensitivity. The rate of SSR was lower than that previously described in the literature.